2019
DOI: 10.1186/s12879-019-4587-x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue infection during pregnancy in Burkina Faso: a cross-sectional study

Abstract: BackgroundDengue fever is prevalent in the world; in recent years, several outbreaks occurred in West Africa. It affects pregnant women. We aimed to assess the consequences of dengue fever on pregnant women and their fetuses during dengue epidemic in Burkina Faso.MethodsWe conducted a cross-sectional study from November 1, 2015 to January 31, 2017 in 15 public and private health facilities in Ouagadougou, using secondary data. Immunochromatographic rapid test Duo detecting specific antibodies, immunoglobin M/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 11 publications
1
25
0
2
Order By: Relevance
“…We screened only those women for inclusion in our study who presented with fever, thereby reducing the number of false positive cases due to serologic positivity solely, which could have confounded the results of our study. Symptoms of dengue observed in our study were similar to symptoms observed in other studies on pregnant and non-pregnant women with dengue [ 14 16 ] with myalgia and arthralgias present in more than 90% of women.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We screened only those women for inclusion in our study who presented with fever, thereby reducing the number of false positive cases due to serologic positivity solely, which could have confounded the results of our study. Symptoms of dengue observed in our study were similar to symptoms observed in other studies on pregnant and non-pregnant women with dengue [ 14 16 ] with myalgia and arthralgias present in more than 90% of women.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have demonstrated rates of thrombocytopenia in pregnant women with dengue between 48–100%. [ 8 , 10 , 14 , 17 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations support evidence previously documented [ 5 , 7 ]. After 2010, severe dengue cases have been increasingly reported in different countries, including Burkina Faso [ 79 ], Côte d’Ivoire [ 80 ], Djibouti [ 30 ], the Republic of Sudan [ 81 ], Senegal [ 22 ], and Tanzania [ 31 ]. The previous report shows that these countries have experienced continuous active DENV transmission in the past decade [ 5 ].…”
Section: Discussionmentioning
confidence: 99%